Another shipment of six short-period giant planets from TESS. Issue 2 (28th February 2023) - Rodriguez, Joseph E; Quinn, Samuel N; Vanderburg, Andrew; Zhou, George; Eastman, Jason D; Thygesen, Erica; Cale, Bryson; Ciardi, David R; Reed, Phillip A; Oelkers, Ryan J; Collins, Karen A; Bieryla, Allyson; et al.
ABSTRACT: We present the discovery and characterization of six short-period, transiting giant planets from NASA's Transiting Exoplanet Survey Satellite (TESS) – TOI-1811 (TIC 376524552), TOI-2025 (TIC 394050135), TOI-2145 (TIC 88992642), TOI-2152 (TIC 395393265), TOI-2154 (TIC 428787891), and TOI-2497 (TIC 97568467). All six planets orbit bright host stars (8.9 < G < 11.8, 7.7 < K < 10.1). Using a combination of time-series photometric and spectroscopic follow-up observations from the TESS Follow-up Observing Program Working Group, we have determined that the planets are Jovian-sized ( RP = 0.99–1.45 RJ ), have masses ranging from 0.92 to 5.26 MJ, and orbit F, G, and K stars (4766 ≤ Teff ≤ 7360 K). We detect a significant orbital eccentricity for the three longest-period systems in our sample: TOI-2025 b ( P = 8.872 d, 0.394^+0.035_-0.038 ), TOI-2145 b ( P = 10.261 d, e = 0.208^+0.034_-0.047 ), and TOI-2497 b ( P = 10.656 d, e = 0.195^+0.043_-0.040 ). TOI-2145 b and TOI-2497 b both orbit subgiant host stars (3.8 < log g <4.0), but these planets show no sign of inflation despite very high levels of irradiation. The lack of inflation may be explained by the high mass of the planets; 5.26^+0.38_-0.37 MJ (TOI-2145 b) and 4.82 ± 0.41 MJ (TOI-2497 b). These six new discoveries contribute to the larger community effort to use TESS to create a magnitude-complete, self-consistent sample of giant planets with well-determined parameters for future detailed studies.